EFEKTIVITAS MODEL GROUP INVESTIGATION PADA HASIL BELAJAR BISNIS RITEL SISWA KELAS XI SMK KARYA MANDIRI - Rita Aryani; Agustiyani Agustiyani (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The objectives of this research are to identify the different types of taboo words and to describe the functions of taboo words as they are used by characters in the Euphoria Season 2 TV show. The descriptive qualitative method was used in this research because the data is in words rather than numbers. This study's primary theory is that of Michael Swan (2005) and Timothy Jay (1992). The researcher discovered four types of taboo words after classifying 50 data of taboo words in Euphoria Season 2 TV Series, namely lavatory 4 data (8%), private parts of body 17 data (34%), religion 12 data (24%), and sexual activity 17 data (34%). Meanwhile, from those 85 data of taboo words, the researcher found some functions of taboo words anger and/or frustration 14 data (16%), descriptive-evaluative 40 data (47%), joking 9 out data (11%), surprise 6 data (7%), and sarcastic irony or insult 16 data (19%).